Back Cover: Harvesting Solar Light with Crystalline Carbon Nitrides for Efficient Photocatalytic Hydrogen Evolution (Angew. Chem. Int. Ed. 41/2014). Issue 41 (19th August 2014) - Bhunia, Manas K.; Yamauchi, Kazuo; Takanabe, Kazuhiro
<x xml:space="preserve">Abstract</x> Metal‐free photocatalysts for visible‐light‐driven H2 evolution that are inexpensive are coveted for energy production. K. Takanabe and co‐workers show in their Communication on page 11001 ff. that a family of crystalline carbon nitrides (CNs) obtained by supramolecular aggregation and ionic melt polycondensation gives excellent photocatalytic H2 evolution. Controlling the amount and arrangements of dopants in the CN structure enables a substantial amount of visible light to be harvested and enhances the photocatalytic performance.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>